Hypothermia due to Antipsychotic Medication: A Systematic Review - Zonnenberg, Cherryl; Bueno-de-Mesquita, Jolien M.; Ramlal, Dharmindredew; Blom, Jan Dirk (Frontiers in Psychiatry, 2017)
Background Hypothermia is a rare, but potentially fatal adverse effect of antipsychotic drug (APD) use. Although the opposite condition, hyperthermia, has been researched extensively in the context of the malignant antipsychotic syndrome, little is known about hypothermia due to APDs. Objective This study aimed to review the literature on hypothermia in the context of APD use, and formulate implications for research and clinical care. Methods A systematic search was made in PubMed and Ovid Medline. Results The literature search yielded 433 articles, including 57 original case descriptions of hypothermia developed during APD use with non-toxic plasma levels. All cases together indicate that the risk of developing hypothermia is highest during the 7 days following initiation, or increase in dosage, of APDs, especially in the presence of additional predisposing factors, such as advanced age, exposure to cold, adjuvant use of benzodiazepines, and (subclinical) hypothyroidism. In addition, data derived from drug-monitoring agencies suggest that the prevalence of APD-related hypothermia is at least 10 times higher than suggested by the literature. Conclusion We conclude that health-care professionals need to monitor the body temperature of patients starting with (an increased dose of) APDs for a duration of 7–10 days to prevent hypothermia, especially in the presence of multiple risk factors. Moreover, systematic studies are needed to establish the actual prevalence of APD-related hypothermia as well as the relative risk for individual APDs.